2019
DOI: 10.1089/ees.2018.0244
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Transport Simulation of Fracture Channelization and Transmissivity Evolution

Abstract: Underground fractures serve as flow conduits, and they may produce unwanted migration of water and other fluids in the subsurface. An example is the migration and leakage of greenhouse gases in the context of geologic carbon sequestration. This study has generated new understanding about how acids erode carbonate fracture surfaces and the positive feedback between reaction and flow. A two-dimensional reactive transport model was developed and used to investigate the extent to which geochemical factors influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 58 publications
(77 reference statements)
1
29
0
Order By: Relevance
“…After injecting synthetic hydraulic fracturing fluid through a Marcellus shale core without acid, Vankeuren et al reported that the absence of acid-induced calcite dissolution resulted in net fracture volume reductions due to mixing-induced barite precipitation, which could either constrict flow or complement proppants to maintain fracture apertures over longer time frames (Vankeuren et al, 2017). Conversely, dissolution in excess of precipitation can lead to asperity removal and fracture compaction (Ellis et al, 2013;Elsworth & Yasuhara, 2010) or channelization and fracture opening (Deng & Peters, 2019;Luquot & Gouze, 2009). In addition to competing reactions, precipitates could be impacted by changes in environmental conditions such as temperature and pressure swings that were not explicitly evaluated in this study.…”
Section: 1029/2019jb018864mentioning
confidence: 99%
“…After injecting synthetic hydraulic fracturing fluid through a Marcellus shale core without acid, Vankeuren et al reported that the absence of acid-induced calcite dissolution resulted in net fracture volume reductions due to mixing-induced barite precipitation, which could either constrict flow or complement proppants to maintain fracture apertures over longer time frames (Vankeuren et al, 2017). Conversely, dissolution in excess of precipitation can lead to asperity removal and fracture compaction (Ellis et al, 2013;Elsworth & Yasuhara, 2010) or channelization and fracture opening (Deng & Peters, 2019;Luquot & Gouze, 2009). In addition to competing reactions, precipitates could be impacted by changes in environmental conditions such as temperature and pressure swings that were not explicitly evaluated in this study.…”
Section: 1029/2019jb018864mentioning
confidence: 99%
“…When the particles accumulate at pore throats, they can exert important control on the flow field, and thus on the dissolution localization. This issue can be circumvented by assuming an inert silicate matrix and thus capping the upper porosity of elemental units in a simulation (Deng et al, ; Deng & Peters, ). In a related paper, we discussed this issue in the context of how these mechanical impacts disrupt the positive feedback loop (Yang, Hakim, et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the general composition of fracture surfaces, the amount and distribution of reactive minerals on fracture surfaces plays an important role in controlling the reactive evolution of fractures 26,27 and is not well understood, often considered to be simply reflective of the bulk mineralogy. 25,26,41 In this work, we analyzed the role of mineralogy in controlling fracture formation by considering the abundance and distribution of minerals on fracture surfaces. Our goal was to improve our ability to predict reactive fracture evolution and understand its implications for subsurface CO 2 sequestration.…”
Section: ■ Introductionmentioning
confidence: 99%